Pengembangan Branding dan Pangsa Pasar Pada Industri Kreatif "Batik Tugiran" Pandak - Puspita Dewi Wulaningrum; Hanifah Rahmi Fajrin (Abdimas Universal, 2022)
The Covid-19 pandemic has reduced public interest in the tourism sector, which has caused a lack of buyer interest in the creative industry sector. Micro, Small and Medium Enterprises (MSMEs) Batik craftsmen "Batik Tugiran" are one of the MSMEs that are affected. This service aims to stimulate the economy of MSMEs engaged in the creative industry which have been significantly affected by the pandemic, especially for MSMEs, Tugiran batik craftsmen. The result of this service is handling for aspects of market share and branding. Branding development in the form of making product logos, making signboards, making road signs, and designing packaging improvements. Meanwhile, the development of the online sector market share is carried out by utilizing social media Instagram and the Shopee marketplace.